Didáctica y su incidencia en los aprendizajes de lectoescritura en los estudiantes de básica elemental de la unidad educativa “pedro Vélez Moran”, cantón el Empalme, provincia del Guayas - Bermello Intriago, Luisana Gabriela (2016)
The teaching is one of the branch within the Pedagogy that specializes in techniques and teaching methods designed to capture the patterns of educational theories. Being a pedagogical scientific discipline whose focus turn out to be all the elements involved in the learning process of a person, so it was determined that literacy is directly related to all learning processes of students from elementary basic Education Unit Pedro Vélez Morán, it will benefit the authorities, teachers and students. The theoretical foundation was based on issues related to teaching and its impact directly on their learning. It began with a literature and field research, using techniques signing, surveys and checklists, whose data were tabulated and processed according to descriptive statistics, analysis and interpretation of whose conclusions and recommendations were obtained. The proposal is a simple document where guide educational games was shaped to strengthen the process of literacy in elementary students basic, same that was developed taking into account the following components was prepared: The analysis of the feasibility, the foundation, the action plan, the methodology to be applied, and a series of papers valid at the time of learning games teach their classes, which allow you to measure the process of literacy development. This guide educational games guide the implementation and execution of literacy professionals said Education Unit.